Chinese herbal medicine combined with oxaliplatin-based chemotherapy for advanced gastric cancer: A systematic review and meta-analysis of contributions of specific medicinal materials to tumor response - Tan, Ying; Wang, Heping; Xu, Bowen; Zhang, Xiaoxiao; Zhu, Guanghui; Ge, Yuansha; Lu, Taicheng; Gao, Ruike; Li, Jie (Frontiers in Pharmacology, 2022)
Introduction: The incidence and mortality of gastric cancer ranks among the highest, and the 5-year survival rate of AGC is less than 10%. Currently, chemotherapy is the main treatment for AGC, and oxaliplatin is an important part of the commonly used chemotherapy regimen for AGC. A large number of RCTs have shown that CHM combined with oxaliplatin-based chemotherapy can improve ORR and DCR, reduce the AEs of chemotherapy. There is currently a lack of systematic evaluation of the evidence to account for the efficacy and safety of CHM combined with oxaliplatin-based chemotherapy in AGC. Therefore, we carried out this study and conducted the sensitivity analysis on the herbal composition to explore the potential anti-tumor efficacy. Methods: Databases of PubMed, EMBASE, CENTRAL, WOS, CBM, CNKI, the Wanfang database, and the Chinese Scientific Journals Database were searched from their inception to April 2022. RCTs evaluating the efficacy of CHM combined with oxaliplatin-based chemotherapy on AGC were included. Stata 16 was used for data synthesis, RoB2 for quality evaluation of included RCTs, and GRADE for quality of synthesized evidence. Additional sensitivity analysis was performed to explore the potential anti-tumor effects of single herbs and combination of herbs. Results: Forty trials involving 3029 participants were included. Most included RCTs were assessed as “Some concerns” of risk of bias. Meta-analyses showed that compare to oxaliplatin-based chemotherapy alone, that CHM combined with oxaliplatin-based chemotherapy could increase the ORR by 35% [RR = 1.35, 95%CI (1.25, 1.45)], and DCR by 12% [RR = 1.12, 95% CI (1.08, 1.16)]. Subgroup analysis showed that compare to SOX, FOLFOX, and XELOX regimens alone, CHM plus SOX, CHM plus FOLFOX, and CHM plus XELOX could significantly increase the ORR and DCR. Conclusion: Synthesized evidence showed moderate certainty that CHM plus oxaliplatin-based chemotherapy may promote improvement in tumor response in AGC. CHM treatment is safe for AGC. Specific combinations of herbs appeared to produce higher contributions to ORR than the herb individually. To support this conclusion, these seven herbs are worthy of further clinical research.